Bone‐forming capacity of adult human nasal chondrocytes. Issue 6 (16th February 2015) - Pippenger, Benjamin E; Ventura, Manuela; Pelttari, Karoliina; Feliciano, Sandra; Jaquiery, Claude; Scherberich, Arnaud; Walboomers, X Frank; Barbero, Andrea; Martin, Ivan
Abstract Nasal chondrocytes (NC) derive from the same multipotent embryological segment that gives rise to the majority of the maxillofacial bone and have been reported to differentiate into osteoblast‐like cells in vitro. In this study, we assessed the capacity of adult human NC, appropriately primed towards hypertrophic or osteoblastic differentiation, to form bone tissue in vivo. Hypertrophic induction of NC‐based micromass pellets formed mineralized cartilaginous tissues rich in type X collagen, but upon implantation into subcutaneous pockets of nude mice remained avascular and reverted to stable hyaline‐cartilage. In the same ectopic environment, NC embedded into ceramic scaffolds and primed with osteogenic medium only sporadically formed intramembranous bone tissue. A clonal study could not demonstrate that the low bone formation efficiency was related to a possibly small proportion of cells competent to become fully functional osteoblasts. We next tested whether the cues present in an orthotopic environment could induce a more efficient direct osteoblastic transformation of NC. Using a nude rat calvarial defect model, we demonstrated that (i) NC directly participated in frank bone formation and (ii) the efficiency of survival and bone formation by NC was significantly higher than that of reference osteogenic cells, namely bone marrow‐derived mesenchymal stromal cells. This study provides a proof‐of‐principle that NC have the plasticity to convert into bone cells and thereby represent an easily available cell source to be further investigated for craniofacial bone regeneration.